1997
DOI: 10.1182/blood.v89.12.4378
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Generation by Apoptotic Vascular Smooth Muscle Cells

Abstract: Thrombin activation requires assembly of a prothrombinase complex of activated coagulation factors on an anionic phospholipid surface, classically provided by activated platelets. We have previously shown that anionic phosphatidylserine is exposed by rat vascular smooth muscle cells (VSMCs) undergoing apoptosis after serum withdrawal. In this study, using a chromogenic assay, we have shown thrombin generation by apoptotic VSMCs expressing c-myc (VSMC-myc) with an area under the thrombin-generation curve (AUC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(52 citation statements)
references
References 32 publications
0
50
0
2
Order By: Relevance
“…The protocol was modified from the method reported by Flynn et al (1997). Briefly, blood from healthy individuals was used to prepare platelet-poor plasma by centrifugation at 3000 g for 15 min.…”
Section: Thrombin Generation Assaymentioning
confidence: 99%
“…The protocol was modified from the method reported by Flynn et al (1997). Briefly, blood from healthy individuals was used to prepare platelet-poor plasma by centrifugation at 3000 g for 15 min.…”
Section: Thrombin Generation Assaymentioning
confidence: 99%
“…We have observed that NB4 cells in culture generate larger amounts of thrombin than any other leukemic cell line. 16 Using the method of Flynn et al, 17 cell suspensions were mixed with defibrinated plasma, Russell's viper venom, and the coagulation process was activated with calcium chloride. The thrombin generated was determined by chromogenic substrate assay.…”
Section: Thrombin Generationmentioning
confidence: 99%
“…Apoptosis of monocytes releases large amounts of the cytokine IL-1b (Miwa et al 1998); apoptotic cells are phagocytosed by binding to receptors such as CD14 (lipopolysaccharide receptor) ligation of which activates phagocytes (Devitt et al 1998). Additionally, apoptotic cells expose the inner lea¯et phospholipid phosphatidylserine externally, conferring procoagulant activity (Flynn et al 1997).…”
Section: Apoptosis Versus Necrosismentioning
confidence: 99%
“…Firm evidence for either of these proposals is not vet available. Apoptotic VSMCs and endothelial cells may also promote thrombosis directly, by exposure of phosphatidylserine on their surface which may promote the formation of prothrombinase and therefore thrombin (Flynn et al 1997). The potency of this property in vivo is unknown but the ability to generate thrombin is likely to be a universal property of apoptotic cells.…”
Section: Apoptosis Signalling Pathways In Vascular Smooth Muscle Cellsmentioning
confidence: 99%